Advance Care Planning and Care Coordination for People With Parkinson's Disease and Their Family Caregivers—Study Protocol for a Multicentre, Randomized Controlled Trial - Meinders, Marjan J.; Gentile, Giovanni; Schrag, Anette E.; Konitsiotis, Spiros; Eggers, Carsten; Taba, Pille; Lorenzl, Stefan; Odin, Per; Rosqvist, Kristina; Chaudhuri, K. Ray; Antonini, Angelo; Bloem, Bastiaan R.; et al. (Frontiers in Neurology, 2021)
Background: Parkinson's disease (PD) is a progressive neurodegenerative disease with motor- and non-motor symptoms. When the disease progresses, symptom burden increases. Consequently, additional care demands develop, the complexity of treatment increases, and the patient's quality of life is progressively threatened. To address these challenges, there is growing awareness of the potential benefits of palliative care for people with PD. This includes communication about end-of-life issues, such as Advance Care Planning (ACP), which helps to elicit patient's needs and preferences on issues related to future treatment and care. In this study, we will assess the impact and feasibility of a nurse-led palliative care intervention for people with PD across diverse European care settings. Methods: The intervention will be evaluated in a multicentre, open-label randomized controlled trial, with a parallel group design in seven European countries (Austria, Estonia, Germany, Greece, Italy, Sweden and United Kingdom). The “PD_Pal intervention” comprises (1) several consultations with a trained nurse who will perform ACP conversations and support care coordination and (2) use of a patient-directed “Parkinson Support Plan-workbook”. The primary endpoint is defined as the percentage of participants with documented ACP-decisions assessed at 6 months after baseline (t1). Secondary endpoints include patients' and family caregivers' quality of life, perceived care coordination, patients' symptom burden, and cost-effectiveness. In parallel, we will perform a process evaluation, to understand the feasibility of the intervention. Assessments are scheduled at baseline (t0), 6 months (t1), and 12 months (t2). Statistical analysis will be performed by means of Mantel–Haenszel methods and multilevel logistic regression models, correcting for multiple testing. Discussion: This study will contribute to the current knowledge gap on the application of palliative care interventions for people with Parkinson's disease aimed at ameliorating quality of life and managing end-of-life perspectives. Studying the impact and feasibility of the intervention in seven European countries, each with their own cultural and organisational characteristics, will allow us to create a broad perspective on palliative care interventions for people with Parkinson's disease across settings. Clinical Trial Registration:www.trialregister.nl, NL8180.